The metabolic syndrome and retinal microvascular signs in a Japanese population: the Funagata study. Issue 2 (26th October 2007) - Kawasaki, R; Tielsch, J M; Wang, J J; Wong, T Y; Mitchell, P; Tano, Y; Tominaga, M; Oizumi, T; Daimon, M; Kato, T; Kawata, S; Kayama, T; et al.
Abstract : Aims: To determine the relationship of metabolic syndrome and its components with retinopathy and other retinal microvascular signs in a Japanese population. Methods: The Funagata study recruited 1961 (53.3% of eligible) Japanese aged 35 or older. The metabolic syndrome was diagnosed primarily using definitions of the International Diabetes Federation. Retinopathy and retinal microvascular signs were assessed from fundus photographs. Retinal arteriolar and venular diameters were measured using a computer-assisted programme. Results: Data were available for analysis in 1638 persons for retinopathy and retinal microvascular signs and 921 persons for retinal vessel diameters. Various components of the metabolic syndrome were associated with retinal microvascular signs: a larger waist circumference was associated with wider venular diameter and retinopathy lesions; a higher blood pressure level was associated with focal arteriolar narrowing, arteriovenous nicking, enhanced arteriolar wall reflex and narrower arteriolar diameter; and a higher triglyceride level was associated with enhanced arteriolar wall reflex. Overall, persons with the metabolic syndrome were more likely to have retinopathy (odds ratio 1.64, 95% CI: 1.02 to 2.64) and wider venular diameter 4.69 μm (95% CI: 1.20 to 8.19 μm) than persons without the metabolic syndrome. Conclusion: We report associations of metabolic syndrome components with retinopathy and wider venular diameter in Japanese adults. These data suggest that metabolic abnormalities, indicated by metabolic syndrome components, are associated with microvascular changes in the retina. There was no synergistic effect of the metabolic syndrome on retinal microvascular changes beyond its individual components.